Academic freedom and doctoral research traditions in higher education in post-apartheid South Africa: Why is PhD a philosophical struggle? - Mathebula, T. (South African Journal of Higher Education, 2025)
From the beginning of doctoral studies, there are three broad traditions that define research in universities: empirical research that is well-known, conceptual research that is merely talked about and philosophical research that is unknown to doctoral students in universities. Given this setting, the Constitution of the Republic of South Africa (1996, 8)[1] and the Higher Education Act (Department of Education 1997, 1–2)[2] make provision for academic freedom and scholarly research in institutions of higher learning in South Africa. Using the University of the Witwatersrand (Wits) as a case study, the article shows how academic freedom is undermined by doctoral definition, doctoral teaching and doctoral writing that are primarily empirical, partially conceptual, and covertly philosophical. This is problematic considering that academic freedom and university autonomy are not irreconcilable but, rather, are closely and jointly connected. To ‘safeguard’ academic freedom, I reposition doctoral research in universities in general on four philosophical planes steered by universities themselves. These are: 1) the clarification of the concept PhD itself—freedom of clarity; 2) the development of ‘self-governing’ doctoral students—freedom to choose and decide without institutional influence; 3) the recognition of a single philosophical style of doctoral research—freedom to pursue knowledge and promote the public good; and 4) the promotion of new scholarship—freedom to rethink and re-imagine future scholars. Given its conceptual-philosophical nature, the article proceeds on the basis of conceptual clarity, analysis of the problem and rigorous argument—this approach does not adopt a theoretical frame, collect data, make findings, and draw conclusions. In the end, I argue for the primacy of philosophical research to be preserved at universities in post-apartheid South Africa.